2015
DOI: 10.1587/elex.12.20150911
|View full text |Cite
|
Sign up to set email alerts
|

A column-parallel clock skew self-calibration circuit for time-resolved CMOS image sensors

Abstract: This letter reports a column-parallel clock skew self-calibration circuit for time-resolved (TR) CMOS image sensors. In TR CMOS imagers, as the time resolution increases, the skew of gating clock between pixels becomes a difficult problem because the clock skew causes the reduction of measurable maximum range in particular pixels or unmeasurable pixels. To calibrate the skew in short time, a column-parallel skew self-calibration circuit based on two-stage delay line and a dual clock tree is proposed. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This challenge is mainly noticed with the variable-resistor array delay element (Zhang and Kaneko 2015 ; Maymandi-Nejad and Sachdev 2005 ). Nonetheless, this drawback may not be applied provided that proper design techniques are utilized, as in the case with the digitally-controlled SCI delay element implemented by (Miao et al 2015 ) which has shown to produce fine and linear delay steps within a relatively wide delay range. The digitally-controlled delay elements have the upper hand when good process portability, short design time, simple and robust design, and good power management are considered together in the design.…”
Section: Digitally-controlled Delay Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…This challenge is mainly noticed with the variable-resistor array delay element (Zhang and Kaneko 2015 ; Maymandi-Nejad and Sachdev 2005 ). Nonetheless, this drawback may not be applied provided that proper design techniques are utilized, as in the case with the digitally-controlled SCI delay element implemented by (Miao et al 2015 ) which has shown to produce fine and linear delay steps within a relatively wide delay range. The digitally-controlled delay elements have the upper hand when good process portability, short design time, simple and robust design, and good power management are considered together in the design.…”
Section: Digitally-controlled Delay Elementsmentioning
confidence: 99%
“…Programmable delay lines with sub-gate delay resolution have been realized using many circuit topologies and techniques. They mainly involve: changing the capacitive loading (SCI) mechanism reported in (Schidl et al 2012 ; Abas et al 2007a ; Pao-Lung et al 2005 ; Miao et al 2015 ) and some of the current-starving delay-controlling techniques reported in (Maymandi-Nejad and Sachdev 2005 ; Saint-Laurent and Swaminathan 2001 ; El Mourabit et al 2012 ) which are mentioned earlier in the third and fourth sections of this paper, delay difference between two delay paths (sometimes called VDL) (Xanthopoulos 2009 ; Guang-Kaai et al 2000 ; Nuyts et al 2014 ), employing phase interpolation technique through, for example, utilizing DLLs as delay lines (Xanthopoulos 2009 ; Yang 2003 ), utilizing a capacitor charging along with comparators controlled by a DAC (Suchenek 2009 ; Klepacki et al 2015 ), and utilizing an analog differential buffer (Nuyts et al 2014 ).…”
Section: Open Research Issues and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar problems arise in time resolved CMOS image sensors and timeinterleaved ADC, the influence of clock skew on the accuracy of time resolution is very important. To solve this problem, column parallel skew calibration circuits have been proposed and demonstrated its effectiveness [26,27,28]. A statistics-based background calibration and digital calibration scheme for timing skew is employed in timeinterleaved flash ADC [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…This modeling aims to clarify the current issues of range resolution toward further improved range resolution. For short calibration times, background skew calibration is implemented using a column-parallel digital delay-locked loop (DLL) and a dual clock tree structure [34]. In this paper, the skew calibration is applied to the three-tap lock-in pixel.…”
Section: Introductionmentioning
confidence: 99%